1994
DOI: 10.1063/1.468340
|View full text |Cite
|
Sign up to set email alerts
|

The recovery of polymer melts after shear and elongational flows

Abstract: This work examines the constrained recoil after steady shear flow and the free recovery after steady elongational flow of monodisperse polymer melts. Calculations are performed in the framework of the Curtiss-Bird theory using both conventional numerical integrations and nonequilibrium Brownian dynamics. The latter approach is shown to have significant advantages, particularly at high shear or elongational rates. The predicted curves of recovery as a function of shear rate exhibit an unusual maximum for which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 12 publications
0
12
0
1
Order By: Relevance
“…It has been used in its polydisperse generalization to describe the Weissenberg rod-climbing experiment by Lodge et al (1988) and recoil of polymer melts after cessation of shear and elongational flows by Borgbjerg & de Pablo (1994). It has been used in its polydisperse generalization to describe the Weissenberg rod-climbing experiment by Lodge et al (1988) and recoil of polymer melts after cessation of shear and elongational flows by Borgbjerg & de Pablo (1994).…”
Section: The Curtiss-bird Modelmentioning
confidence: 99%
“…It has been used in its polydisperse generalization to describe the Weissenberg rod-climbing experiment by Lodge et al (1988) and recoil of polymer melts after cessation of shear and elongational flows by Borgbjerg & de Pablo (1994). It has been used in its polydisperse generalization to describe the Weissenberg rod-climbing experiment by Lodge et al (1988) and recoil of polymer melts after cessation of shear and elongational flows by Borgbjerg & de Pablo (1994).…”
Section: The Curtiss-bird Modelmentioning
confidence: 99%
“…Only recently have molecular models been used to study recovery flows, which occur in extrusion and other industrially important processes. Borgbjerg et al 2 have presented a Brownian dynamics study of recovery following simple steady shear flow in a parallel-plate geometry using the polymer melt kinetic theory of Curtiss and Bird. 3 These authors showed that the recovery predicted by the Curtiss-Bird model exhibits a maximum at high shear rates.…”
Section: Introductionmentioning
confidence: 99%
“…For polymer melts, the Curtiss-Bird model is used as a constitutive equation. The stochastic differential equations for the Curtiss-Bird model in a dimensionless form are described by (1), (2) …”
Section: Stochastic Approachmentioning
confidence: 99%
“…Moreover, the dynamics of mesoscale structures can be analyzed using the coupling of stochastic simulations and macroscopic flow computations. One of famous micro-macro approaches is CONNFFESSIT proposed byÖttinger et al (1), (2) .…”
Section: Introductionmentioning
confidence: 99%